Preparation method of material capable of realizing tetracycline adsorption and visible light degradation
By comparing UIO-66 with nickel doping and black phosphorus sheet layer, BP@UiO-66-0.9Ni nanomaterial was prepared, which solved the problems of low light utilization efficiency of UIO-66 and easy oxidation of black phosphorus, achieving high efficiency Tetracycline adsorption and visible light degradation significantly improve the effect of wastewater treatment.
Patent Information
- Application Number
- CN202411502954.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2024-12-17
AI Technical Summary
The metal organic frame UIO-66 has low light utilization efficiency and poor response to visible light, and the problem of easy oxidation of black phosphorus limits its application in wastewater treatment.
By performing transition metal nickel doping and monocarboxylic benzoic acid regulation on UIO-66, combined with black phosphorus sheet layer, a nanomaterial BP@UiO-66-0.9Ni was prepared by solvothermal method and ultrasonic composite technology to achieve tetracycline efficient adsorption and visible light degradation.
The material's removal efficiency of tetracycline under visible light reached more than 99%, and its adsorption capacity was 358 mg g-1. It has good acid-base stability and anion coexistence tolerance. The catalytic efficiency remained above 67% after four cycle tests.
Smart Images

Figure CN119140072A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of antibiotic wastewater treatment, and in particular relates to a method for preparing a material capable of realizing tetracycline adsorption and visible light degradation. Background Art
[0002] Since tetracycline (TC) was discovered in the 1940s, it has been widely used to prevent and treat human and animal infections due to its broad-spectrum antibacterial properties and low cost and availability, and is added to animal feed as a growth promoter. However, due to its stable structure, tetracycline cannot be completely metabolized by humans or animals. More than 75% of TCs continue to be excreted in active form through the urine and feces of humans and animals and released into the environment, causing a large number of negative impacts on the ecological environment and human health. In particular, residual tetracycline in the water environment can induce the production of resistant microorganisms and resistance genes, increase human drug resistance and produce resistant bacteria. The problem of bacterial resistance has been assessed by the World Health Organization as one of the biggest threats to human health in the 21st century. Therefore, the development of environmentally friendly and efficient tetracycline wastewater treatment technology has become an urgent problem to be solved.
[0003] So far, a variety of different physical, chemical and biological technologies have been developed for the treatment of wastewater containing new persistent organic pollutants, including chemical precipitation, biodegradation, membrane filtration, electrochemical treatment and Fenton reaction. However, these technologies are often limited by cost or efficiency. In the existing technology, adsorption is one of the most commonly used wastewater treatment methods because of its environmental protection, high efficiency and simplicity. Photocatalytic oxidation can convert the potential risks of various pollutants in water into compounds with low biological toxicity or even non-toxicity. This technology has the characteristics of mild conditions, green environmental protection, high efficiency and economy, wide application range, no secondary pollution and easy availability of catalysts.
[0004] Metal-organic frameworks (MOFs) have attracted extensive attention in wastewater treatment due to their unique properties endowed by large specific surface area, abundant active adsorption sites, and regular and easily adjustable pore structures. In particular, UIO-66 has a series of excellent properties, such as high thermal stability, acid-base stability, and chemical stability in a variety of organic solvents and water environments. However, for monomer UIO-66, it still has the disadvantages of low light utilization efficiency, poor response to visible light, and easy recombination of photogenerated electron-hole pairs.
[0005] Compared with other precious metals commonly used in the field of catalysis, black phosphorus (BP) has obvious cost advantages. In addition, black phosphorus has unique properties such as excellent charge mobility, unique two-dimensional layered structure, and direct band gap with layer-dependent tunable properties. Therefore, black phosphorus can show strong light-matter interaction in the visible light to infrared light range, and is an attractive candidate material in the field of photocatalysis. However, each phosphorus atom in black phosphorus has a highly active lone pair of electrons, which easily reacts with oxygen and water adsorbed on the surface of few-layer black phosphorus (FLBP), resulting in the oxidation of black phosphorus. Summary of the invention
[0006] [Technical issues]
[0007] The problem to be solved by the present invention is that the metal organic framework UIO-66 has low light utilization efficiency, poor response to visible light, and easy recombination of photogenerated electron-hole pairs. Each phosphorus atom in black phosphorus has a highly active lone pair of electrons, which can easily react with oxygen and water adsorbed on the surface of black phosphorus, leading to oxidation of black phosphorus, limiting its application in wastewater treatment.
[0008] [Technical solution]
[0009] In order to solve the above problems, the present invention provides a method for preparing a material that can achieve tetracycline adsorption and visible light degradation, which simultaneously implements three strategies: transition metal nickel doping of UIO-66, adjusting the manufacturing framework defects with monocarboxylic acid benzoic acid, and constructing a heterojunction with black phosphorus sheets. By sequentially adding reactants and ultrasonically compounding them one by one, controlling the amount of reactant addition, an integrated nanomaterial with high-efficiency adsorption performance for tetracycline and photocatalytic removal under visible light is synthesized by a solvothermal method.
[0010] The present invention provides a method for preparing a material capable of achieving tetracycline adsorption and visible light degradation, which specifically comprises the following steps:
[0011] (1) Preparation of few-layer black phosphorus: Platinum wire and black phosphorus are used as anode and cathode, respectively. The cathode and anode are placed in an electrolyte, and electrochemical stripping is assisted by ultrasound. Finally, few-layer black phosphorus is obtained by step-by-step centrifugation.
[0012] (2) The few-layer black phosphorus obtained in step (1) is placed in DMF to obtain a few-layer black phosphorus suspension, ZrCl4 and NiCl2·6H2O are added in sequence, and finally 1,4-phthalic acid (H2BDC) and benzoic acid are added, and ultrasonic dissolution is performed to prepare a material that can achieve tetracycline adsorption and visible light degradation through a solvothermal method.
[0013] In one embodiment of the present invention, in step (1), the electrolyte contains 8 to 15 mg mL -1 Tetrabutylammonium bromide (TBAB) in DMF.
[0014] In one embodiment of the present invention, in step (1), the parameters of the stepwise centrifugation are: first centrifugation at 2500-5000 rpm for 7-12 min, and then centrifugation at 11000-13000 rpm for 18-25 min.
[0015] In one embodiment of the present invention, in step (2), the concentration of the few-layer black phosphorus in the few-layer black phosphorus suspension is 0.05-0.1 mg mL -1 .
[0016] In one embodiment of the present invention, in step (2), the mass ratio of the few-layer black phosphorus to ZrCl4 is 1:56-140, and the molar ratio of ZrCl4 to NiCl2·6H2O is 1:0.25-1.
[0017] In one embodiment of the present invention, in step (2), the molar ratio of 1,4-phthalic acid to benzoic acid is 1:10-15.
[0018] In one embodiment of the present invention, in step (2), the molar ratio of ZrCl4 to 1,4-phthalic acid is 1:0.8-1.2.
[0019] In one embodiment of the present invention, in step (2), the reaction conditions of the solvothermal method are heating at 105-130° C. for 22-28 h.
[0020] In one embodiment of the present invention, in step (2), after ZrCl4 and NiCl2·6H2O are added in sequence, ultrasonic treatment is performed for 50 to 90 minutes and 20 to 50 minutes, respectively.
[0021] The present invention also provides a material prepared by the above method and capable of achieving tetracycline adsorption and visible light degradation.
[0022] The present invention also provides application of the above-mentioned material in the field of water treatment.
[0023] [Beneficial Effects]
[0024] 1. The present invention first adds Zr 4+ , Zr 4+ Ultrasonic bonding with FLBP forms a covalent bond, making Zr 4+ preferentially occupy the FLBP surface sites, and then add Ni 2+Ultrasound is performed to form a certain binding effect, and finally organic ligands and benzoic acid are added for doping. This synthesis method can achieve FLBP being inside and UIO-66 growing along the surface of FLBP, so as to evenly coat black phosphorus to avoid oxidation and provide an efficient charge transfer channel for photogenerated electrons; at the same time, the transition metal nickel and benzoic acid present in the growth process of UIO-66 simultaneously dope the MOF crystals in two aspects.
[0025] 2. The simultaneous excessive addition of ZrCl4 and H2BDC enables UIO-66 to form independent crystalline particles in addition to encapsulating BP.
[0026] 3. The material prepared by the present invention has a TC of 358 mg g -1 The adsorption capacity of BP@UiO-66-0.9Ni was 20.6 times and 75.2 times higher than that of UiO-66 monomer, respectively, and it could remove more than 99% of the initial concentration of tetracycline hydrochloride after visible light irradiation degradation. The adsorption and visible light catalytic degradation abilities of BP@UiO-66-0.9Ni were 20.6 times and 75.2 times higher than those of UiO-66 monomer, respectively, and it could also be used in the ultra-wide range of pH 2 to 12 and up to 20 mmol L -1 Under the coexistence conditions of anions, the removal effect can be stably maintained at more than 94%.
[0027] 4. After four cycle tests, the catalytic efficiency of BP@UiO-66-0.9Ni is still greater than 67%, which shows a certain degree of recyclability.
[0028] 5. The method of the present invention only needs to utilize clean light energy, does not need to consume ultraviolet light energy, has simple reaction equipment, wide application range, mild conditions, high efficiency and economy, and the catalyst is cheap and easy to obtain. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 (a) XRD diffraction images and (b) FTIR images of a series of samples of few-layer black phosphorus (BPNPs), UIO-66, BP@UiO-66, UiO-66-0.9Ni and BP@UiO-66-XNi; (c) nitrogen adsorption-desorption isotherms of UIO-66, BP@UiO-66, UiO-66-0.9Ni and BP@UiO-66-0.9Ni;
[0030] Figure 2 (a) SEM and (b) high-resolution transmission electron microscopy images of few-layer black phosphorus (BPNPs); (c) SEM image of monomer UIO-66; (d) SEM image (ef) TEM image and (gl) energy spectrum of the composite material BP@UiO-66-0.9Ni;
[0031] Figure 3(a) The adsorption performance of UIO-66, BP@UiO-66, UiO-66-0.9Ni and BP@UiO-66-XNi series materials on tetracycline hydrochloride; (b) The effect of the amount of BP@UiO-66-0.9Ni on the adsorption capacity and removal efficiency of tetracycline hydrochloride; (c) The effect of the coexisting anions (Cl - 、SO4 2- and CO3 2- ) on the adsorption of tetracycline hydrochloride by BP@UiO-66-0.9Ni; (d) the effect of the initial pH of the tetracycline hydrochloride solution on the adsorption performance of BP@UiO-66-0.9Ni and the Zeta potential of BP@UiO-66-0.9Ni in tetracycline hydrochloride solution at different pH;
[0032] Figure 4 The effect of initial TC concentration on the adsorption performance of BP@UiO-66-0.9Ni;
[0033] Figure 5 (a and b) The degradation effect of a series of catalysts on tetracycline hydrochloride under visible light; (c) The pseudo-first-order reaction constant k of different materials; (d) The cycle experiment of BP@UiO-66-0.9Ni photocatalyst on the degradation of tetracycline hydrochloride under visible light; (e) The total removal efficiency of BP@UiO-66-0.9Ni for tetracycline hydrochloride at different pH values; (f) The total removal efficiency of BP@UiO-66-0.9Ni for tetracycline hydrochloride due to coexisting anions;
[0034] Figure 6 (a) XRD patterns and (b) FTIR patterns of BP@UiO-66-0.9Ni before use and after recycling. DETAILED DESCRIPTION
[0035] Example 1
[0036] (1) Few-layer black phosphorus was prepared in large quantities by electrochemical rapid stripping combined with ultrasound, including: -1 A two-phase DC power supply was introduced into the DMF electrolyte of TBAB, and platinum wire and block black phosphorus (50 mg) were used as anode and cathode, respectively. The electrolyte was maintained at 20 V for 30 min to quickly obtain the initially peeled black phosphorus flakes. Then, all the electrolyte was transferred to a sealed bottle and ultrasonicated in an ice bath for 3 h. The block black phosphorus that was not completely peeled off was removed at centrifugal strengths of 3000 rpm for 10 min and 11000 rpm for 20 min, respectively. The peeled black phosphorus flakes were collected, washed thoroughly with methanol, and then vacuum dried at 25 ° C overnight to obtain a few-layer black phosphorus. The dried few-layer black phosphorus was placed in DMF and configured to 2 mg mL -1 A few-layer black phosphorus suspension is prepared and then dispersed by ultrasonication for later use;
[0037] (2) 1 mL of the above-mentioned rare-layer black phosphorus suspension was diluted to 30 mL, 1.2 mmol ZrCl4 was added, and then ultrasonic treatment was performed for 60 min to make Zr 4+ Adsorbed on the BP surface, 0.9 mmol NiCl2·6H2O was added and ultrasonicated again for 30 min, and 1.2 mmol H2BDC and 13.6 mmol benzoic acid were further added to the mixture and ultrasonically dissolved. Then, the mixture was transferred to a polytetrafluoroethylene-lined high-pressure reactor, heated at 120 °C for 24 h, and after natural cooling, washed with DMF and methanol for multiple times, respectively, and placed at 60 °C for vacuum drying for 24 h.
[0038] Example 2
[0039] Basically the same as Example 1, the amount of NiCl2·6H2O added in step (2) is 0.3 mmol, and the rest of the contents are basically the same as described in Example 1.
[0040] Example 3
[0041] Basically the same as Example 1, the amount of NiCl2·6H2O added in step (2) is 0.5 mmol, and the rest of the contents are basically the same as described in Example 1.
[0042] Example 4
[0043] Basically the same as Example 1, the amount of NiCl2·6H2O added in step (2) is 0.7 mmol, and the rest of the contents are basically the same as described in Example 1.
[0044] Comparative Example 1
[0045] Basically the same as Example 1, except that the amount of NiCl2·6H2O added in step (2) is 0 mmol, and the rest of the contents are basically the same as those described in Example 1.
[0046] Examples 1 to 4 and Comparative Example 1 prepared gradient nickel-doped samples by changing the amount of nickel ion added, and the prepared materials were marked as BP@UiO-66-XNi, where X represents the millimolar amount of nickel element added to the reaction system. The materials prepared in Examples 1 to 4 and Comparative Example 1 were named BP@UiO-66-0.9Ni, BP@UiO-66-0.3Ni, BP@UiO-66-0.5Ni, BP@UiO-66-0.7Ni, and BP@UiO-66, respectively.
[0047] Comparative Example 2
[0048] The preparation of UIO-66 specifically includes: dissolving ZrCl4 (1 mmol) and H2BDC (1 mmol) in N,N-dimethylformamide (DMF, 30 mL) and thoroughly dissolving by ultrasonication. The mixture is then transferred to a polytetrafluoroethylene-lined autoclave and heated at 120°C for 24 hours to obtain a solid product.
[0049] Comparative Example 3
[0050] The preparation of UIO-66-0.9Ni specifically includes: dissolving ZrCl4 (1 mmol), H2BDC (1 mmol), and NiCl2·6H2O (0.9 mmol) in N,N-dimethylformamide (DMF, 30 mL) and thoroughly dissolving by ultrasonication. The mixture is then transferred to a polytetrafluoroethylene-lined autoclave and heated at 120°C for 24 hours to obtain a solid product.
[0051] Performance characterization:
[0052] The prepared materials were characterized by X-ray diffraction, Fourier transform infrared spectroscopy, and specific surface area and pore size analysis. Figure 1 (a) is the X-ray diffraction pattern of few-layer black phosphorus, Examples 1 to 4, and Comparative Examples 1 to 3. It can be seen from the spectrum that the obvious sharp peaks at 7.4° and 8.5° correspond to the (111) and (200) crystal planes, respectively, indicating that UIO-66 is correctly synthesized. The diffraction peaks at 17.1° and 34.3° represent the (020) and (040) planes of few-layer black phosphorus, respectively. No XRD peaks related to BP were found in all samples containing BP. The XRD peaks of all MOF samples are similar to the spectrum of UIO-66 monomer, which is attributed to the lower content of BP and the uniform and complete wrapping of MOF crystals on the black phosphorus surface.
[0053] Figure 1 (b) is the FTIR spectrum of the prepared sample. After the growth of UIO-66, the FTIR spectrum of the material has almost no significant change due to the low BP content and Ni doping amount in the material. -1 The vibration peaks at 1584 and 1404 cm are consistent with the Zr-O bond and are affected by the Ni doping and the presence of BP. -1 The characteristic peaks are caused by the symmetrical and asymmetrical stretching of the carboxyl groups in the organic ligands, indicating that UIO-66 contains carboxyl groups on terephthalic acid. -1 The characteristic peak at 1505cm represents the stretching vibration of C=O in the carboxyl ester group of terephthalic acid ligand. -1 The characteristic peaks seen at are caused by the vibration of the C=C bond in the benzene ring. The analysis of the above characteristic peaks indicates that UIO-66 is correctly synthesized.
[0054] Figure 1 (c) is the nitrogen adsorption-desorption isotherm. As shown in the figure, a typical type I adsorption isotherm is shown, and BP@UiO-66-0.9Ni has a more obvious adsorption hysteresis loop in the range of higher relative pressure, which indicates that there is a certain mesoporous distribution in the composite material, indicating that the Zr-MOF system material is a microporous and mesoporous material. Compared with the initial UIO-66, the specific surface area, pore size and pore volume of the BP@UiO-66-0.9Ni sample have increased significantly, which is more conducive to improving the adsorption capacity, providing more active sites for the reaction of the substrate, and is conducive to the photocatalytic degradation.
[0055] The microstructure and crystal structure of the samples were observed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Figure 2 a and Figure 2 As shown in Figure c, pure BP monomer and UIO-66 monomer exhibit a nanosheet stacking structure with a smooth surface and a cubic morphology of irregular octahedral small particle agglomeration, respectively. The diameter of UIO-66 monomer particles is mainly around 130nm. HR-STEM image of BP ( Figure 2 b) shows that the spacing of its lattice fringes is 0.26nm, corresponding to the (040) plane of few-layer black phosphorus. The diffraction peak at 34.3° in the X-ray diffraction (XRD) image of the few-layer BP nanosheets is a clear peak corresponding to the orthorhombic BP crystal structure. The morphology of the BP@UiO-66-0.9Ni sample shows that relatively dispersed and independent MOF particles grow uniformly and densely on the surface of larger black phosphorus sheets ( Figure 2 df). Due to the interaction between BP and Zr 4+ The growth of MOF crystals occurs on the BP surface due to the pre-binding, resulting in a significant increase in the thickness of the material. At the same time, the dense and uniform protective shell formed by the formation of MOF on the surface of black phosphorus further avoids the oxidation of black phosphorus. This shows that the pre-formation of Zr-P bonds is an important step in the formation of dense packaging. In addition, due to the addition of excess Zr in the reaction system, 4+ and H2BDC, and Ni doping was performed at the same time, and a conventional uniformly dispersed cubic MOF particle was formed. In addition, no obvious particles were found on the MOF structure in the transmission electron microscopy image of BP@UiO-66-0.9Ni, indicating that no other nickel-containing substances were attached to the MOF surface, confirming the results of the X-ray diffraction spectrum. The stable structure of the internal black phosphorus skeleton and the MOF protective shell is conducive to the light capture, charge separation, and more reactive sites between the catalyst and the substrate.
[0056] The BP@UiO-66-0.9Ni sample was analyzed by energy spectrum under transmission electron microscope ( Figure 2gl), it can be confirmed that all elements of BP@UiO-66-0.9Ni are evenly distributed, further indicating that Ni is evenly doped in the crystal during the MOF growth process, and that the MOF crystals evenly cover the BP sheets. Based on the above analysis, the correct synthesis of the material can be confirmed.
[0057] Adsorption experiment:
[0058] The adsorption experiment was carried out in a multi-channel photocatalytic reaction system (PerfectLight PCX-50C). The basic adsorption conditions were: 50 mL of reaction system, 30 mg L of initial tetracycline hydrochloride solution concentration, and 100 mg L of iodine. -1 10 mg of adsorbent was added to the system to start the adsorption process. The system was continuously stirred magnetically and samples were collected regularly. The TC concentration was determined by high performance liquid chromatography (Waterse 2695) through a 0.22 μm filter membrane.
[0059] The pH of the TC solution system was adjusted using HCl and NaOH to study the acid-base stability of BP@UiO-66-0.9Ni. The coexistence of anions was verified in TC solutions containing different concentrations of NaCl, NaCO3, and NaSO4.
[0060] The adsorption capacity of the prepared Zr-MOF system material for tetracycline hydrochloride is as follows: Figure 3 All samples showed rapid adsorption from 0 to 10 min, and the adsorption trend slowed down after 10 min. The adsorption capacity of each sample for tetracycline hydrochloride showed the following pattern: BP@UiO-66-0.9Ni (148.3 mg g -1 )>BP@UiO-66-0.7Ni(146.4mg g -1 )>BP@UiO-66-0.5Ni(143.7mg g -1 )>BP@UiO-66-0.3Ni(140.5mg g -1 )>BP@UiO-66(92.2mg g -1 )>UiO-66-0.9Ni(42.8mg g -1 )>UiO-66(7.2mg g -1 ). Among them, UIO-66 has the lowest adsorption capacity. The adsorption capacity of the samples doped with nickel or composited with black phosphorus increased, while the adsorption capacity of the samples composited with black phosphorus and doped with nickel increased significantly, and the adsorption capacity increased with the increase of Ni doping content. Among them, BP@UiO-66-0.9Ni has the strongest adsorption capacity, and its adsorption capacity is 20.6 times that of the initial UiO-66.
[0061] In order to discuss the adsorption capacity of BP@UiO-66-0.9Ni in more detail, the usage of the adsorbent BP@UiO-66-0.9Ni was optimized and verified. The usage of BP@UiO-66-0.9Ni was increased from 0.1 g L -1 Increase to 0.5 g L -1 As the amount of adsorbent used increases, the corresponding adsorption sites increase, and the removal efficiency of tetracycline hydrochloride increases ( Figure 3 b) However, due to the interaction of adsorption active sites, the amount of adsorbent used is negatively correlated with the total adsorption capacity. When the amount of BP@UiO-66-0.9Ni is 0.2 g L -1 At the same time, it has a high adsorption capacity (138.1 mg g -1 ) and removal efficiency (93.8%).
[0062] Generally speaking, the presence of various anions in wastewater will affect the actual adsorption performance. Figure 3 c shows different concentrations of Cl - 、SO4 2- and CO3 2- The influence of BP@UiO-66-0.9Ni on the adsorption and removal of tetracycline hydrochloride. The experimental results show that the adsorption capacity of BP@UiO-66-0.9Ni for tetracycline decreases with the increase of ion concentration. The order of influence of coexisting ions on adsorption is: CO3 2- >SO4 2- >Cl - The coexisting inorganic anions will form competitive adsorption with tetracycline hydrochloride molecules, and the anions with larger negative charges will bind more strongly to the adsorbent. 2- The effect on adsorption capacity is greater, probably because CO3 2- The presence of leads to an increase in the pH of the solution system, which in turn affects the actual adsorption capacity. This was verified in the subsequent pH effect experiment.
[0063] The initial pH of the reaction system will have a significant impact on the existence state of BP@UiO-66-0.9Ni and tetracycline hydrochloride molecules. Figure 3 As shown in Figure d, a series of initial pH values of tetracycline hydrochloride were used to verify the effect of BP@UiO-66-0.9Ni on the adsorption performance of tetracycline. BP@UiO-66-0.9Ni has good adsorption performance for tetracycline hydrochloride in a wide range of acid-base changes (the adsorption capacity is greater than 145 mg g -1 ), only when the initial pH was 2 or 12, the adsorption capacity of BP@UiO-66-0.9Ni for tetracycline hydrochloride decreased significantly, but it could still be maintained at 100 mg g -1 High adsorption capacity.
[0064] By measuring the Zeta potential of BP@UiO-66-0.9Ni in tetracycline hydrochloride solution at different pH values, the adsorption characteristics of the adsorbent on tetracycline hydrochloride were further analyzed. The experiment showed that when the pH was below 6, the surface of BP@UiO-66-0.9Ni was positively charged, and when the pH was greater than 8, the surface charge of BP@UiO-66-0.9Ni was negatively charged. At the same time, under different pH conditions, tetracycline hydrochloride also showed different ionic forms at different pH values. Including cationic form (pH < 3.3), neutral form (3.3 < pH < 7.7) and anionic form (pH > 7.7). Therefore, when the pH is 2 or 12, tetracycline hydrochloride and BP@UiO-66-0.9Ni both carry strong charges of the same type, and electrostatic repulsion is the main force, which reduces the adsorption performance. The high adsorption capacity at pH values between 4 and 10 indicates that the π-π bond interaction between the aromatic structure of tetracycline hydrochloride molecules and the organic ligands of MOF is dominant at this time, making the adsorption capacity unaffected by the pH value of the solution.
[0065] The initial concentration of tetracycline hydrochloride has a great influence on the adsorption process, such as Figure 4 As shown in Figure 2, the adsorption of tetracycline hydrochloride at different initial concentrations on BP@UiO-66-0.9Ni was studied at pH 10. The initial tetracycline hydrochloride concentration ranged from 10 to 90 mg L -1 With the increase of TC concentration, the adsorption capacity continued to increase. Within 180 min, the initial concentration was 10-50 mg L -1 The TC solution can remove more than 97% by adsorption alone. Even at a high concentration of 90 mg L -1 The TC solution can also remove more than 79% after adsorption, and the adsorption capacity can reach 358 mg g at 180 min. -1 This is because a higher initial TC concentration has a higher concentration gradient driving force. All sample groups experienced rapid adsorption within 10 min. The BP@UiO-66-0.9Ni particles have abundant adsorption sites, which may be the reason for the high initial adsorption rate. As the adsorption continues, the repulsive force between the TC molecules in the solution and the TC molecules adsorbed on the surface of the BP@UiO-66-0.9Ni nanoparticles causes the adsorption to slow down and eventually reach an adsorption-desorption equilibrium.
[0066] Visible light degradation experiment:
[0067] The visible light degradation experiment was also completed in a multi-channel photocatalytic reaction system. The visible light was provided by a 10W LED (100mW cm -2 ) was provided by a parallel multi-channel Vlight lamp panel. 10 mg of catalyst was added to TC solution (50 ml, 30 mg L-1 ), and magnetic stirring was continued for 60 min to reach adsorption-desorption equilibrium, and then the visible light source was turned on to start the degradation reaction. Samples were taken out at fixed time intervals and filtered through a 0.22 μm filter to detect TC concentration.
[0068] After 60 minutes of dark adsorption, the TC concentration after adsorption equilibrium was taken as the zero point, and the photocatalytic degradation experiment of tetracycline hydrochloride was carried out under visible light to study the photocatalytic degradation performance of the material. Figure 5 As shown in ab, in the absence of any catalyst, tetracycline hydrochloride is insensitive to light, has stable properties, and hardly any degradation occurs. The UIO-66 material only shows weak adsorption and negligible degradation effects; the degradation capabilities of samples composited with black phosphorus and doped with Ni are improved to varying degrees. The removal efficiency of samples combined with black phosphorus and doped with Ni is significantly enhanced, and the catalytic efficiency is further enhanced with the increase of Ni content. BP@UiO-66-0.9Ni has the highest adsorption and degradation efficiency at the same time, adsorbing and removing 95.45% of tetracycline hydrochloride within 60 minutes, and then removing the remaining 90.2% (1.2% for UiO-66 monomer) by visible light degradation, and the total removal rate of tetracycline hydrochloride reaches 99.55%. The photocatalytic kinetics are calculated by the pseudo-first-order kinetic model. As Figure 5 As shown in c, the catalytic efficiency of BP@UiO-66-0.9Ni for tetracycline hydrochloride is as high as 0.039 min -1 , the degradation reaction rate of BP@UiO-66-0.9Ni is 136.1 times higher than that of the initial UiO-66 monomer, and is 4.9 times and 5.9 times that of BP@UiO-66 and UiO-66-0.9Ni.
[0069] The recyclable use of catalysts is crucial for practical applications. The used materials were collected and ultrasonically cleaned, vacuum dried at 60°C and used in the next round of recycling experiments under the same conditions. Figure 5 As shown in Figure d, the total removal efficiency decreased during the second reuse, decreasing by about 23%. Considering the super strong adsorption performance of BP@UiO-66-0.9Ni for TC, TC was also retained in the pores during cleaning, which was difficult to remove, resulting in blockage of the catalyst pores, thereby reducing the removal efficiency of TC. The reduction in catalytic efficiency may also be due to the inevitable oxidation loss of some BP during the photocatalytic process. However, in subsequent cycle experiments, the material was stable as a whole and the catalytic efficiency was no longer significantly reduced. After four cycle tests, the catalytic efficiency was still greater than 67%. In addition, the X-ray diffraction spectrum and Fourier transform infrared transform spectrum of the recycled BP@UiO-66-0.9Ni were compared with those of the unused BP@UiO-66-0.9Ni ( Figure 6). After recycling, the XRD and FTIR spectra of BP@UiO-66-0.9Ni did not change significantly, indicating that the catalytic material itself is stable and has a certain degree of recyclability.
[0070] Considering the complex composition of actual wastewater, we verified the acid-base stability and anion coexistence stability of the synthetic material. As discussed above, BP@UiO-66-0.9Ni has shown good acid-base stability during the adsorption process, and the adsorption efficiency is reduced only at pH 2 or 12. Figure 5 As shown in Figure e, the visible light degradation process following the dark adsorption process can still degrade and remove the remaining TC. In the ultra-wide range of pH 2 to 12, BP@UiO-66-0.9Ni shows excellent removal effect on tetracycline. The pKa value of TC is relatively low and is stable in an acidic environment. Therefore, the total removal rate of TC is the lowest in a strongly acidic environment with a pH value of 2, but it can still achieve an excellent effect of 89.95%. The removal rate of TC under other conditions remained above 97%. Similar to the results of acid-base stability, the coexistence of anions also has little effect on the removal of TC by BP@UiO-66-0.9Ni ( Figure 5 f) High concentration of CO3 2- When TC molecules are present, the adsorption removal efficiency is reduced due to its competition with TC molecules, but the subsequent visible light degradation is still unaffected and the remaining unadsorbed part is removed. Regardless of the anion type and concentration, the total removal efficiency of all sample groups remains above 94%.
[0071] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing a material capable of achieving tetracycline adsorption and visible light degradation, characterized in that: The specific steps include: (1) Preparation of few-layer black phosphorus: Electrochemical exfoliation was used to assist ultrasonic treatment of black phosphorus, and few-layer black phosphorus was prepared by step-by-step centrifugation; (2) The few-layer black phosphorus obtained in step (1) is placed in DMF to obtain a few-layer black phosphorus suspension, ZrCl4 and NiCl2·6H2O are added in sequence, and finally 1,4-phthalic acid and benzoic acid are added to obtain a material that can achieve tetracycline adsorption and visible light degradation through a solvothermal method.
2. The method for preparing a material capable of achieving tetracycline adsorption and visible light degradation according to claim 1, characterized in that: In step (1), the electrochemical stripping method uses a platinum wire as an anode, black phosphorus as a cathode, and an electrolyte containing 8 to 15 mg mL -1 Tetrabutylammonium bromide DMF solution; the parameters of the stepwise centrifugation are: first centrifugation at 2500-5000 rpm for 7-12 min, and then centrifugation at 11000-13000 rpm for 18-25 min.
3. The method for preparing a material capable of achieving tetracycline adsorption and visible light degradation according to claim 1, characterized in that: In step (2), the concentration of the few-layer black phosphorus in the few-layer black phosphorus suspension is 0.05-0.1 mg mL -1 .
4. The method for preparing a material capable of achieving tetracycline adsorption and visible light degradation according to claim 1, characterized in that: In step (2), the mass ratio of the few-layer black phosphorus to ZrCl4 is 1:56-140.
5. The method for preparing a material capable of achieving tetracycline adsorption and visible light degradation according to claim 1, characterized in that: In step (2), the molar ratio of ZrCl4 to NiCl2·6H2O is 1:0.25-1.
6. The method for preparing a material capable of achieving tetracycline adsorption and visible light degradation according to claim 1, characterized in that: In step (2), the molar ratio of 1,4-phthalic acid to benzoic acid is 1:10-15; the molar ratio of ZrCl4 to 1,4-phthalic acid is 1:0.8-1.
2.
7. The method for preparing a material capable of achieving tetracycline adsorption and visible light degradation according to claim 1, characterized in that: In step (2), the reaction conditions of the solvothermal method are heating at 105-130° C. for 22-28 hours.
8. The method for preparing a material capable of achieving tetracycline adsorption and visible light degradation according to claim 1, characterized in that: In step (2), ZrCl4 and NiCl2·6H2O are added in sequence, and then ultrasonic treatment is performed for 50 to 90 minutes and 20 to 50 minutes, respectively.
9. A material capable of achieving tetracycline adsorption and visible light degradation prepared by the method of any one of claims 1 to 8.
10. Use of the material according to claim 9 in the field of water treatment.
Citation Information
Cited By
Carbon felt-based Ni-coated UiO-66 / GO catalytic electrode, preparation method and application thereof, and product containing carbon felt-based Ni-coated UiO-66 / GO catalytic electrode
CN119797511A
Preparation method and application of CoO / black phosphorus catalyst
CN120054551A
